Influences of Casing Wear on Mechanical Behavior of Packer Element. (September 2020) - Wang, Jieli; Gao, Baokui; Ma, Chao; Hu, Tianxiang; Chen, Xingwang
Abstract: Packer element is made of hyperelastic rubber, and its mechanic performance determines the packer's sealing effect. In oil field, casing wear is often found and in some special circumstance the packer has to set at worn casing section. In order to study the effect of casing wear on element mechanical behavior, contact pressure between element and casing with crescent-shaped wear notch is calculated by use of commercial ANSYS software. The influences of notch depth and diameter of drill pipe joint on contact pressure are discussed in detail. The results show that the contact pressure has a saddle-shaped distribution along axial direction similar to that without wear. But minimum contact pressure decreases rapidly when the notch depth increases. And a larger diameter of drill pipe joint can give rise to lower contact pressure near the notch.